1995
DOI: 10.1111/j.1348-0421.1995.tb02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Hepatitis A Virus Antibody Response Elicited in Mice by Different Forms of a Synthetic VP1 Peptide

Abstract: Peptide VP1 (11-25) of the capsid of hepatitis A virus was synthesized by the Fmoc-polyamide solid phase method, and administered to mice in different forms: (1) free, (2) encapsulated in multilamellar liposomes, (3) coupled to keyhole limpet hemocyanin (KHL), and (4) incorporated into a tetrameric branched lysine core. The highest anti-VP1 peptide responses were generated by synthetic peptides entrapped into liposomes and coupled to KLH. No anti-HAV response was generated with the free peptide, while all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…4B), but and DPPC:SA (9:1) monolayers, the insertion process could the area per molecule does not change in the presence of be fitted to Eq. [1] independently of the initial surface pres-MAP 4 VP1 above 10 mN/m. This can be interpreted as if sure, with maximum pressure increase values as high as 15 the peptide was squeezed out of the monolayer at this high mN/m in SA monolayers at p i Å 5 mN/m (Table 1).…”
Section: Insertion Of Map 4 V P1 Into Monolayersmentioning
confidence: 96%
See 2 more Smart Citations
“…4B), but and DPPC:SA (9:1) monolayers, the insertion process could the area per molecule does not change in the presence of be fitted to Eq. [1] independently of the initial surface pres-MAP 4 VP1 above 10 mN/m. This can be interpreted as if sure, with maximum pressure increase values as high as 15 the peptide was squeezed out of the monolayer at this high mN/m in SA monolayers at p i Å 5 mN/m (Table 1).…”
Section: Insertion Of Map 4 V P1 Into Monolayersmentioning
confidence: 96%
“…Interaction of bioactive tide antigens are weakly immunogenic when administered peptides with membranes stabilizes certain conformations in free form; however, it has been shown that constructs of on the peptide that meet receptor requirements better than the structures in solution (11,12). This is particularly im- 1 To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous immunological assays carried out in our group, peptides encapsulated into multilamellar vesicles (MLV liposomes) were used to enhance the immune response evoked by synthetic peptides. 35,36 Consequently, in order to evaluate the conformational behavior of the synthetic peptide entrapped in MLV liposomes, CD characterization of this peptide was attempted in the present work. Not surprisingly, the high lipid content of the preparations led to light scattering effects and the liposome suspensions were turbid even after exhaustive sonication, which yielded anomalous CD spectra (data not shown).…”
Section: Differences In Secondary Structure Of Hepatitis a Virusmentioning
confidence: 99%
“…The efficiency of liposomes as adjuvants has been established for a great variety of peptide antigens (3)(4)(5)(6)(7). Their ability to enclose antigens in the aqueous compartment, among the hydrophobic chains or covalently coupled to the surface of the vesicles, makes liposomes a versatile tool to be used in the development of peptide immunoadjuvants (8,9).…”
Section: Introductionmentioning
confidence: 99%